GAMBARAN DISFUNGSI SEKSUAL, DISABILITAS, DAN KUALITAS HIDUP PADA PASIEN PASCASTROKE - Hasanul Arifin; Alfansuri Kadri; Yuneldi Anwar (NEURONA, 2019)
A DESCRIPTION OF SEXUAL DYSFUNCTION, DISABILITY, AND QUALITY OF LIFE OF POST-STROKE PATIENTSABSTRACTIntroduction: Sexual function and disability are post-stroke complications that can affect the long-term quality of life. The problem is being neglected, thus cannot be intervened further. There are simple screenings that can be used to detect the disorder.Aim: To determine the characteristics  of sexual dysfunction, disability and quality of life, and also demographic profile of post stroke patients in Neurology Outpatient Clinic at General Hospital Haji Adam Malik, Medan.Method: A cross sectional descriptive study on poststroke patients in Neurology Outpatient Clinic of General Hospital Adam Malik, Medan between March and July 2018. Subjects were asked to fill three questionnaires; Changes in Sexual Functioning Questionnaire (CSFQ-14) to assess sexual dysfunction, Stroke-Specific Quality of Life (SS-QoL-12) to assess quality of life, and Barthel Index (BI) and modified Rankin Scale (mRS) to assess disability.Results: We identified 45 subjects and the mean of age was 60.27+10.12 years, mostly men (75.6%) and was suffered from ischemic stroke (95.6%). Majority of the subjects (93.3%) were reported of having sexual dysfunction, some have symptoms of disability (35.6%) and full dependence (44.5%). The quality of life was relatively better in male, especially in the physical domain.Discussion: In post stroke population, the prevalence of sexual dysfunction is 93.3%, mostly affected male patients. Majority of the subjects were independent and without significant disability. The quality of life was relatively better in male and the lowest value related to health was the power domain.Keywords: Disability, post-stroke, quality of life, sexual dysfunctionABSTRAKPendahuluan: Salah satu komplikasi pascastroke adalah gangguan fungsi dan disabilitas seksual yang dapat memengaruhi kualitas hidup jangka panjang. Namun hal ini masih terabaikan, hingga tidak dapat diintervensi lebih lanjut. Terdapat beberapa skrining sederhana yang dapat digunakan untuk mendeteksi gangguan tersebut.Tujuan: Untuk mengetahui gambaran disfungsi seksual, disabilitas, dan kualitas hidup pada penderita pascastroke di rawat jalan Neurologi RSUP Haji Adam Malik, Medan.Metode:  Penelitian  deskriptif  dengan  studi  potong  lintang  pada  pasien  pascastroke  di  Poliklinik  Neurologi RSUP Haji Adam Malik, Medan pada bulan Maret–Juli 2018. Subjek diminta mengisi 3 kuesioner, yaitu: Changes in Sexual Functioning Questionnaire (CSFQ-14) untuk menilai perubahan fungsi seksual, Stroke-Specific Quality of Life (SS-QoL-12) untuk menilai kualitas hidup, serta Indeks Barthel (IB) dan modified Rankin Scale (mRS) untuk  menilai disabilitas.Hasil: Didapatkan 45 subjek dengan rerata usia 60,27+10,12 tahun, terutama laki-laki (75,6%) dan menderita stroke iskemik (95,6%). Mayoritas subjek mengalami disfungsi seksual (93,3%), sebagian memiliki gejala disabilitas (35,6%) dan ketergantungan penuh (44,5%). Kualitas hidup relatif lebih baik pada laki-laki dan khususnya pada domain fisik.Diskusi: Didapatkan prevalensi disfungsi seksual sebanyak 93,3% pada pasien pascastroke, terutama laki-laki. Mayoritas subjek pada keadaan mandiri dan disabilitas yang tidak signifikan. Gambaran kualitas hidup secara keseluruhan relatif lebih baik pada laki-laki dengan nilai yang berhubungan dengan kesehatan yang relatif paling rendah adalah domain tenaga.Kata Kunci: Disabilitas, disfungsi seksual, kualitas hidup, pascastroke